Long-term-survival phase cells of Salmonella enteritidis ATCC 13076 exhibit significantly greater tolerance to atmospheric cold plasma treatment of shell eggs - Barry, Kia; Mendonça, Aubrey; Phillips, Gregory J.; Boylston, Terri; Fortes-Da-Silva, Paulo; Brehm-Stecher, Byron; Juneja, Vijay; Wan, Zifan (Frontiers in Food Science and Technology, 2024)
The main objective of this study was to evaluate the tolerance of stationary phase (STAT) and long-term survival phase (LTS) Salmonella Enteritidis ATCC 13076 to atmospheric cold plasma (ACP) in phosphate buffered saline (PBS, pH 7.0) and on shell eggs. Salmonella Enteritidis was cultured in tryptic soy broth supplemented with 0.6% (w/v) yeast extract (35°C) for 20 h (STAT) and 21 days (LTS). Cell morphology was determined by light microscopy. The PBS and shell eggs were inoculated with STAT or LTS cells to obtain ∼7.0 log10 CFU/mL or egg. The ACP was applied at 45 kV (PBS) and 60 kV (shell eggs) for 1–4 min and 1–5 min, respectively. Pathogen survivors were enumerated on thin agar layer (TAL) medium and on xylose lysine tergitol-4 (XLT-4) agar after 48 h of incubation (35°C). For survivors on shell eggs, R2 and mean square error values were obtained using Log-linear with Tail and Weibull models. The STAT cells were predominantly rod-shaped whereas LTS cells were coccoid. In PBS, reductions (log10 CFU/mL) of STAT cells were 1.0, 0.95, 1.45, and 1.44 after exposure to ACP for 1, 2, 3, and 4 min, respectively. In contrast, reductions in LTS cells were significantly lower (p< 0.05) at 0.04 (1 min), 0.06 (2 min) 0.01 (3 min), and 0.11 (4 min). A similar pattern was observed for shell eggs whereby LTS cells exhibited much higher tolerance to ACP than STAT cells (p < 0.05). The Log-linear with Tail model produced a better fit of the survival data for STAT cells; times to achieve a 4- and 5- log reduction were 5.29 and 5.78 min, respectively. Sub-lethal injury occurred in both STAT and LTS survivors; however, differences were not significant (P > 0.05). Additionally, there were no observed differences in shell strength and yolk color between ACP-treated and control eggs. Based on these results, LTS cells of S. Enteritidis are more tolerant to ACP than STAT cells and should be considered when developing process validation protocols involving application of ACP to inactivate Salmonella on shell eggs.